2010
DOI: 10.1007/s00264-010-1149-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical prediction of early fatal outcome following hip fracture in the elderly

Abstract: Hip fracture, a moderate musculoskeletal trauma, is associated with a high postoperative mortality. Most patients are elderly, with comorbid conditions and often with heart disease. The objective of this study was to find out if clinical parameters and analyses of specific muscle enzymes could predict three month postoperative mortality. A total of 302 patients above 75 years of age with hip fracture were consecutively enrolled. Baseline information on age, sex and comorbidity assessed with the American Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…We have earlier found elevated levels of plasma troponin T that correlated with the three-month fatal outcome [11]. In the same population, we showed that affection of the liver, lung and kidney functions in comorbid elderly patients also correlated with fatal outcome [22].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We have earlier found elevated levels of plasma troponin T that correlated with the three-month fatal outcome [11]. In the same population, we showed that affection of the liver, lung and kidney functions in comorbid elderly patients also correlated with fatal outcome [22].…”
Section: Discussionsupporting
confidence: 52%
“…In addition, the surgical trauma caused release of intracellular enzymes such as troponin T and reduced oxygen tension, consistent with damage of heart cells and reduced pulmonary function [11].…”
Section: Introductionmentioning
confidence: 99%
“…A previous retrospective study in a cohort of more than 1,200 HFS patients shows perioperative MI to have occurred in 13.8 % of patients within seven days of surgery, with a subsequent fourfold increase in 30-day mortality [23]; three fourths of those patients were asymptomatic. Recommendations have therefore been made for the routine use of postoperative troponin measurements, despite the absence of symptoms, as an in-hospital preventative strategy to reduce MI related mortality [23][24][25][26]. We found a moderate correlation between pre-existing cardiac disease and early death from acute MI in our cohort of patients.…”
Section: Discussionmentioning
confidence: 66%
“…We read with interest the article of Talsnes et al who concluded that laboratory analyses on cardiospecific troponins, namely, troponin T, provide useful information on the risk of fatal outcome in elderly patients undergoing hip fracture surgery [1]. The development and introduction into routine laboratory practice of assays for measuring cardiospecific troponins has revolutionised the diagnostic approach of patients with chest pain and suspected acute coronary syndrome (ACS).…”
mentioning
confidence: 96%